Use of Planetscope Imagery to Identify Galodo in Sungai Jambu, Pariangan, Tanah Datar, West Sumatra - Putri, Sri Kandi; Pertiwi, Mentari Dian; Arifian, Naf'an (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This study aims to identify and analyze the impact of the Galodo disaster in Sungai Jambu (Pariangan, Tanah Datar, West Sumatra) using PlanetScope satellite imagery. Galodo disasters, which are flash floods that transport materials such as soil and rocks, often occur in mountainous areas and cause significant damage to the environment and infrastructure. Located on the slopes of Mount Marapi, Sungai Jambu is one of the areas prone to galodo due to its geomorphology and high rainfall. The research methodology involved using PlanetScope images before and after the Galodo accident on May 13, 2024. Data processing included radiometric and geometric correction as well as image composite analysis to detect changes in land cover and river flow. The 3-2-1 and 4-3-2 composite images were used to detect changes in vegetation, stream conditions and degraded open land. The results showed significant changes in land cover and river flow due to the Galodo disaster, characterized by increased water turbidity and damaged vegetation. This study confirms the effectiveness of PlanetScope images in monitoring and identifying the impacts of the Galodo disaster. These findings provide important information for post-disaster mitigation and recovery planning and help identify areas that require restoration. Thus, the use of PlanetScope images can improve our understanding of environmental damage caused by disasters and support more effective and sustainable mitigation measures